Five Flavonoids from Lucerne Varieties - Grechana, O. V.; Serbin, A.; Rudnik, A. M.; Saliy, O.; Гречана, Олена Володимирівна; Рудник, Анна Михайлівна (My University, 2023)
Alfalfa (Fabaceae) is known as perennial herbaceous leguminous plant species that originated in southwestern Asia and is used as a folk medicine for the treatment of various ailments. The upper ground part of Lucerne contains phenolic compound such as flavonoids and others, which exhibit biological activities. This study aimed to determine five widely known flavonoids in extracts 20 alfalfa varieties herb at the Ukrainian steppe growing. 50 seeds of the same size were selected from twenty varieties of alfalfa from different countries, and cultivated in controlled areas of the southern part of the Left Bank of Ukraine at the border of forest-steppe and steppe zones (Zaporizhzhya, Ukraine) from April to June, with 15 °C/ 07 °C (day/night), 14 h/10 h (light/dark) and 60–65% relative humidity. The content of flavonoids was found unequable in ethanol extracts. The chemical compositions and their content were assessed by ultrahigh-performance liquid chromatography. The content of five flavonoids was different in the 20 alfalfa varieties raw materials. Umbelliferone was found high in ethanol extract of Mongolian colorful hybrid (Mongolia, 0.23 mg/g). Four sorts have not contained umbelliferone: Кisvardai (Hungary), Nizona (Cuba), Тanhuato (Mexico), and Mesopotamian (Iraq). The leader from cinaroside content was sort Commercial 2-52-75 of UK origin. Routine has been found in the highest quantities in WL 50 from the USA. Ferganska 700 from Uzbekistan was the leader in luteolin content and Кisvardai, Hungary was the leader in an average of kaempferol content (0.030 mg/g). The present article comprises the hierarchical cluster analyses from the data flavonoid assay. In fact, a real method has been obtained for the targeted production of valuable biologically active components with a high content from plant sources.
Keywords: Lucerne; Cultivar; Flavonoids; Hierarchical Clustering